2021
DOI: 10.31258/dli.8.1.p.42-47
|View full text |Cite
|
Sign up to set email alerts
|

Analisis mutu air Danau Area Gelanggang Expo dengan metode indeks pencemaran di kota Jayapura

Abstract: This study aims to determine the current status of lake water quality in the Gelanggang Expo area using the Pollution Index (IP) method. It is found that there has been pollution in Lake Sentani with high concentrations of certain pollutants, such as Nitrite as NO2-N (0.06 - 0.15 mg/L), Phosphate as PO4-P (0.2 - 0.45 mg/L), Sulfide as S-H2S (0.002 - 4.26 mg/L), Cadmium (0.01 - 0.3 mg/L), Chromium valence 6 (0.05 - 0.26 mg/L), Copper (0.02 - 2.15 mg/L), Zinc (0.05 - 0.5 mg/L), Phenolic compounds (1 - 9.53 μg/L)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…The deeper the waters will cause a decrease in water temperature, DO concentration, and pH. The results of research by Prasetia and Walukow (2021) found water temperature, DO, pH, and TDS on the surface waters of Lake Sentani (Gelanggang Expo; St.13 in this study) were 29.6°C, 6.1 mg/L, 8.14, and 69 mg/ L, respectively. These results are relatively the same as the results of this study for the parameters of water temperature, DO, and pH, namely 30.1°C, 6.6 mg/L, and 8.39, respectively.…”
Section: Discussionmentioning
confidence: 48%
“…The deeper the waters will cause a decrease in water temperature, DO concentration, and pH. The results of research by Prasetia and Walukow (2021) found water temperature, DO, pH, and TDS on the surface waters of Lake Sentani (Gelanggang Expo; St.13 in this study) were 29.6°C, 6.1 mg/L, 8.14, and 69 mg/ L, respectively. These results are relatively the same as the results of this study for the parameters of water temperature, DO, and pH, namely 30.1°C, 6.6 mg/L, and 8.39, respectively.…”
Section: Discussionmentioning
confidence: 48%
“…High COD can disrupt the life of aquatic biota and can even cause death in fish and aquatic plants [27]. According to the findings from the research cited in [28], the lake area within the Jayapura City expo arena is categorized as moderately polluted, as determined by the pollution index. This is because seven parameters exceed the quality standard values, namely temperature, BOD, COD, sulfide, lead, copper and phenol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used the pollutant index to measure water quality status, such as the Gili Meno Saltwater Lake on Lombok Island with moderately polluted water quality status (Abdullah, 2021), Situ Parigi in South Tangerang has been moderately polluted (Zharifa, Fachrul, & Hendrawan, 2019), on Area Expo Arena Lake in Jayapura City with moderately polluted water quality status (Prasetia & Walukow, 2021), Rawa Pening Lake in Semarang Regency is already heavily polluted (Piranti et al, 2018). Sunter Lake in Jakarta City is lightly polluted (Saputro, Sunaryo, & Fahdiran, 2020).…”
Section: Water Quality Statusmentioning
confidence: 99%